Respostas
respondido por:
0
f(-2)=-1 e f(3)=4
-2a + b = - 1
3a + b = 4(-1)
-2a + b = -1
-3a - b = -4
-5a = -5(-1) ==> 5a = 5 ==> a = 1
b = - 1 + 2a ==>b = -1+ 2(1) ==>b= - 1+2 ==> b = 1
===================================================
f(x) = x + 1
4 4
-2a + b = - 1
3a + b = 4(-1)
-2a + b = -1
-3a - b = -4
-5a = -5(-1) ==> 5a = 5 ==> a = 1
b = - 1 + 2a ==>b = -1+ 2(1) ==>b= - 1+2 ==> b = 1
===================================================
f(x) = x + 1
4 4
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás